2020
DOI: 10.1021/acs.est.0c00096
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Manganese Oxides as Electrode Materials for Harnessing Salinity Gradient Energy

Abstract: The potential energy contained in the controlled mixing of waters with different salt concentrations (i.e., salinity gradient energy) can theoretically provide a substantial fraction of the global electrical demand. One method for generating electricity from salinity gradients is to use electrode-based reactions in electrochemical cells. Here, we examined the relationship between the electrical power densities generated from synthetic NaCl solutions and the crystal structures and morphologies of manganese oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…also reported that the power output of CFCs with different MnO 2 positively correlated with their respective specific capacitance because high specific capacitance means larger charge storage capacity. 27 Comparison with the power output of CFCs with biochar electrodes (Bio400–700), which had peak power densities in the range of 0.25–0.45 W m –2 ( Figure S12 ), further confirmed that the pseudocapacitance from MnO x was critical for the high power output of MnO x /biochar electrodes.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…also reported that the power output of CFCs with different MnO 2 positively correlated with their respective specific capacitance because high specific capacitance means larger charge storage capacity. 27 Comparison with the power output of CFCs with biochar electrodes (Bio400–700), which had peak power densities in the range of 0.25–0.45 W m –2 ( Figure S12 ), further confirmed that the pseudocapacitance from MnO x was critical for the high power output of MnO x /biochar electrodes.…”
Section: Resultsmentioning
confidence: 72%
“…The Donnan potential resulted from the AEM as Cl – moved from the HC to the LC channel, which was ∼0.08 V for all the concentration flow cells. 11 Therefore, the electrode potential of the cells with BioMn600 and BioMn700 electrodes was 0.07 V, the cell with BioMn500 electrodes was 0.06 V, and the cell with BioMn700 electrodes was 0.05 V. The electrode potential was produced from the activities of Na + with the electrodes via a surface pseudocapacitive reaction ( eq 1 ): 14 , 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multicellular filaments with hundreds of cells arranged end-to-end resulted in the enhanced EET ability to electrodes [ 36 ]. Similarly, given that filamentous C. matruchotii is discovered as an electroactive oral pathogen in this study and some other oral biofilm pathogens such as Streptococcus mutans [ 16 ], Aggregatibacter actinomycetemcomitans [ 6 ], Porphyromonas gingivalis [ 6 ] and Capnocytophaga ochracea [ 38 ] have already been shown to have EET capability are well connected with C. matruchotii , which nucleates the plaque-characteristic consortium according to the spatial organization in oral biogeography [ 17 ], it can be anticipated that long range electron transport is supported by C. matruchotii and the whole oral biofilm is electrically conductive. Based on the previous findings that in the oral polymicrobial biofilm, consortium consists of radially arranged taxa, organized around cells of filamentous Corynebacteria with anaerobic taxa in the interior and facultative or obligate aerobes tend at the periphery of the consortium [ 17 ], we can purpose that this arrangement may support electrically coupled organics oxidation and oxygen reduction in oral polymicrobial biofilm as in the cases of long-range EET in natural environments.…”
Section: Discussionmentioning
confidence: 96%
“…Nanostructured birnessite is of particular interest for aqueous high‐power electrochemical energy storage and desalination applications because it is inexpensive, non‐toxic, and has a high specific capacitance (>100 F g −1 ) in circumneutral aqueous electrolytes [1] . The electrochemical charge storage behavior of birnessite is superior to other manganese oxide polymorphs [1–4] . In desalination systems, birnessite has shown higher reversible salt adsorption capacities as compared to tunneled or amorphous manganese oxides [5–7] .…”
Section: Introductionmentioning
confidence: 99%